Loại bỏ selen trong nước bằng vật liệu zirconi cố định trên than hoạt tính Trà Bắc theo phương pháp thủy nhiệt trong môi trường NH3 - Phương Thảo, Đào Thị; Dương, Bùi Văn (Vietnam Journal of Chemistry, 2017)
In this study, a zirconium based activated carbon was synthesized by hydrothermal method in NH3 medium (Zr/AC/N), it creates a very good adsorbent for selenic. It is shown that the sorbent has a specific surface area of 548.944 m2/g, and a pHpzc of 5.4, the sorption equilbrium can be reached within 6h and the optimal pH is 2 at room temperature. The maximum adsorption capacity of 50.25 mg Se/g was achieved. This material was characterized by using analytical techniques such as TA, XRD, SEM, TEM and BET. Keywords. Adsorbent, Zr4/AC/N3-180-60, selenic.